Advances in endogenous and exogenous opioids : proceedings of the International Narcotic Research Conference (satellite symposium of the 8th International Congress of Pharmacology), held in Kyoto, Japan on July 26-30, 1981 - Takagi, Hiroshi; Simon, Eric J. (Kodansha ; Elsevier Biomedical Press ; Distributors for the US and Canada, Elsevier Science Pub. Co., 1981)
Advances in Endogenous and Exogenous Opioids.